PENGARUH GAYA KEPEMIMPINAN, KEDISIPLINAN DAN PEMBERIAN INSENTIF TERHADAP KINERJA KARYAWAN PT. BARUGA ASRINUSA DEVELOPMENT - Dahlan Dahlan; Andi Jam'an; Agussalim Harrang (COMPETITIVENESS, 2020)
Problems that occur in PT. Baruga Asrinusa Development is a matter of leadership style, this can be seen from the conflict between the company and employees. This conflict occurs due to misunderstanding between superiors and employees. This study aims to find out and analyze the influence of leadership style, discipline, and incentives on employee performance, as well as to know and analyze variables that have a dominant effect on employee performance in PT. Baruga Asrinusa Development. The research was conducted for 3 months from September to November 2018 with a population of 227 people and sampling techniques that are random samples from a population of 50 people who were sampled. The analysis method used in this research is quantitative descriptive method, with double regression testing preceded by performing validity and reliability test of question items of each variable as well as assumption test. The results of this study showed that the coefficient of leadership style influence on employee performance which shows that it has a significant positive effect on employee performance, coefficient of disciplinary influence on employee performance that shows that discipline has a significant positive effect on employee performance, coefficient of effect of incentives on employee performance which indicates that the provision of incentives has a significant positive effect on employee performance. This can be interpreted that the leadership style, discipline, and incentives for employee performance at PT. Baruga Asrinusa Development will increase. And the highest value is the incentive variable so that the variable that has the most influence is the incentive variable. Keywords: leadership style, discipline, incentives, and performance.